Geostatistical Approach and Drone Image Analysis of the Spatial Distribution of Bacterial Leaf Blight in Rice Plants - Hery Nirwanto; Sri Wiyatiningsih; Salsa Bila Ari Nur Izza (The University of Lampung, 2025)
Bacterial leaf blight caused by the bacterium Xanthomonas oryzae is an important disease because it can cause severe damage and can infect the vegetative and generative phases of rice plants. This research was carried out to determine the spatial distribution of leaf blight using a geospatial approach and drone imagery. The results of this research indicate that the distribution of bacterial leaf blight disease on land at the research location tends to be higher in the northern part compared to the southern part of the land. The attack rate value at the end of the observation ranged between 20-68%. The distribution of leaf blight on land can be described through simulations using a geostatistical approach and confirmed by aerial imagery. Aerial imagery, especially binary imagery and kriging imagery, mutually confirm (crosscheck) the occurrence of leaf blight on land. Aerial images that are processed into binary images have the potential to be a remote sensing method that can make it easier to observe the distribution of diseases on land, especially leaf blight. Keywords: Campestris, Drone Imagery, Geospatial, Rice, Xanthomona.